2007
DOI: 10.1139/f06-174
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic data collected during and between bottom trawl stations: consistency and common trends

Abstract: Acoustic data are often collected during bottom trawl surveys. Their use can potentially improve the precision and accuracy of fish abundance estimates if acoustic data collected between trawl stations are consistent with those collected during trawling operations. This question is addressed here through the analysis of 20 bottom trawl surveys (three survey areas and five different survey series) with coincident acoustic measurements during and between trawl stations. Firstly, on-station and underway acoustic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The higher on-station means support the findings of Bez et al (2007). They demonstrated a generally high consistency between on-station and between-station acoustics for several surveys, including the Barents Sea winter survey, using tools like the variogram and a global index of collocation.…”
supporting
confidence: 79%
“…The higher on-station means support the findings of Bez et al (2007). They demonstrated a generally high consistency between on-station and between-station acoustics for several surveys, including the Barents Sea winter survey, using tools like the variogram and a global index of collocation.…”
supporting
confidence: 79%
“…Of the five known studies (including this one) that directly compared the acoustic backscatter between a trawling and a freerunning vessel, one found no difference between the two survey modes (Bez et al, 2007), two reported higher acoustic backscatter while free-running (Ona and Godø, 1990;De Robertis and Wilson, 2006), and two reported higher acoustic backscatter while trawling (this study and . It is not clear why the results from the different studies are so divergent, but it is important to question the implied assumption that any observed differences in the acoustic backscatter between trawling and free-running reflect differences in fish behavior.…”
Section: Discussionmentioning
confidence: 59%
“…Of the studies that have directly compared the acoustic backscatter between a trawling and a free-running vessel, only one reported no difference between the two survey modes (Bez et al, 2007). All others found significant differences but with contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…Besides differences in avoidance reactions due to different light levels or fish diel activity (accounted for by the trawl efficiency coefficient), estimates of b<1 in fact represent a net reduction of the amount of hake biomass available to the trawl, which could be explained by a higher trawl selectivity for the smaller hake present at night-time. Spatial information in acoustic data has been used in the past to increase the precision and accuracy of trawl-based abundance estimates (Bez et al, 2007). The originality of our approach resides in the quantitative study of fish spatial distribution prior to trawl efficiency computations, to control for fish availably effects.…”
Section: Discussionmentioning
confidence: 99%